2023
DOI: 10.3389/fimmu.2023.1135588
|View full text |Cite|
|
Sign up to set email alerts
|

Edwardsiella piscicida infection reshapes the intestinal microbiome and metabolome of big-belly seahorses: mechanistic insights of synergistic actions of virulence factors

Abstract: Uncovering the mechanism underlying the pathogenesis of Edwardsiella piscicida-induced enteritis is essential for global aquaculture. In the present study, we identified E. piscicida as a lethal pathogen of the big-belly seahorse (Hippocampus abdominalis) and revealed its pathogenic pattern and characteristics by updating our established bacterial enteritis model and evaluation system. Conjoint analysis of metagenomic and metabolomic data showed that 15 core virulence factors could mutually coordinate the remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…In this study, we identified the potential of flagella, polar flagella, type 1 fimbriae, and type IV cilia to enhance pathogen movement, transmission, invasion, and colonization. A recent study conducted on gut pathogens in big-belly seahorse ( Hippocampus abdominalis ) also found that the flagella and type IV pili could promote pathogen motility, adherence, and invasion by enhancing the activities of key functional pathways associated with flagella assembly and bacterial chemotaxis within the gut microbiota ( Zhang et al, 2023 ). Both ClpP (with the highest correlation to L. monocytogenes ) and CsrA (with the highest correlation to L. pneumophila ) were also identified as the prevailing VFs within the five groups.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we identified the potential of flagella, polar flagella, type 1 fimbriae, and type IV cilia to enhance pathogen movement, transmission, invasion, and colonization. A recent study conducted on gut pathogens in big-belly seahorse ( Hippocampus abdominalis ) also found that the flagella and type IV pili could promote pathogen motility, adherence, and invasion by enhancing the activities of key functional pathways associated with flagella assembly and bacterial chemotaxis within the gut microbiota ( Zhang et al, 2023 ). Both ClpP (with the highest correlation to L. monocytogenes ) and CsrA (with the highest correlation to L. pneumophila ) were also identified as the prevailing VFs within the five groups.…”
Section: Resultsmentioning
confidence: 99%